AUTOMATED STUDENT ATTENDANCE SYSTEM THROUGH FACE-RECOGNITION USING NVIDIA JETSON AND CUDA TECHNOLOGY - Zulkifli, Ahmad Rashdan (Universiti Teknologi PETRONAS, 2020)
The following report is to discuss about the proposed project of researching today’s modern image and facial recognition technologies that detects human faces and recognizes certain individuals and implementing it into a student attendance management platform. Face recognition is a basic trait owned by humans and is realized into computer technology into many aspects of daily life such as security of accessing personal services or data and for ease of daily activities.